Mediterranean Connections: The Frankish Kingdoms and the Roman Empire (476-756) - Sarti, Laury, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2026)
This monograph challenges the idea that Roman imperial authority in the West ended in 476. It shows how the Frankish realm maintained ties to the empire, with real separation only emerging in the late sixth century. Tracing enduring Frankish-Byzantine diplomacy, shared identities, religious controversy, and trade into the seventh century, it reveals a landscape of continued exchange rather than abrupt decline. Including previously overlooked sources, the study offers a new perspective on Frankish identity, imperial affiliation, and the evolving relationship between Rome, the empire, and the Merovingians from the fifth to the eighth century.